Strong genetic influence on a UK nationwide test of educational achievement at the end of compulsory education at age 16. - Nicholas G Shakeshaft; Maciej Trzaskowski; Andrew McMillan; Kaili Rimfeld; Eva Krapohl; Claire M A Haworth; Philip S Dale; Robert Plomin (PLoS ONE)
We have previously shown that individual differences in educational achievement are highly heritable in the early and middle school years in the UK. The objective of the present study was to investigate whether similarly high heritability is found at the end of compulsory education (age 16) for the UK-wide examination, called the General Certificate of Secondary Education (GCSE). In a national twin sample of 11,117 16-year-olds, heritability was substantial for overall GCSE performance for compulsory core subjects (58%) as well as for each of them individually: English (52%), mathematics (55%) and science (58%). In contrast, the overall effects of shared environment, which includes all family and school influences shared by members of twin pairs growing up in the same family and attending the same school, accounts for about 36% of the variance of mean GCSE scores. The significance of these findings is that individual differences in educational achievement at the end of compulsory education are not primarily an index of the quality of teachers or schools: much more of the variance of GCSE scores can be attributed to genetics than to school or family environment. We suggest a model of education that recognizes the important role of genetics. Rather than a passive model of schooling as instruction (instruere, 'to build in'), we propose an active model of education (educare, 'to bring out') in which children create their own educational experiences in part on the basis of their genetic propensities, which supports the trend towards personalized learning.